2024
DOI: 10.3390/agriculture14020294
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Offers Insights into the Impact of In Vitro Drought Stress on Strawberry Cultivars

Özhan Şimşek

Abstract: This study aimed to assess the susceptibility of three strawberry cultivars (“Festival”, “Fortuna”, and “Rubygem”) to drought stress induced by varying polyethylene glycol (PEG) concentrations in the culture medium. Plantlets were cultivated on a solid medium supplemented with 1 mg/L BAP, and PEG concentrations (0, 2, 4, and 6 mg/L) were introduced to simulate drought stress. Morphological changes were observed, and morphometric analysis was conducted. Additionally, artificial neural network (ANN) analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
4
5
0
Order By: Relevance
“…Our research underscores the superior predictive performance of RF in the TIS culture, particularly in forecasting the number of microcorms, shoots, and roots. This finding is consistent with the literature such as Şimşek [35], which highlighted the robustness of RF in detecting water stress effects in strawberries, and Aasim et al [37], which identified the efficacy of RF in predicting germination and morphological traits in hemp seedlings. The ability of RF to In the general view of machine learning applications within the agricultural domain, particularly focusing on plant tissue culture, our study delves into the comparative effectiveness of the four models used in two distinct culture systems, namely the TIS and semisolid medium.…”
Section: Machine Learning Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…Our research underscores the superior predictive performance of RF in the TIS culture, particularly in forecasting the number of microcorms, shoots, and roots. This finding is consistent with the literature such as Şimşek [35], which highlighted the robustness of RF in detecting water stress effects in strawberries, and Aasim et al [37], which identified the efficacy of RF in predicting germination and morphological traits in hemp seedlings. The ability of RF to In the general view of machine learning applications within the agricultural domain, particularly focusing on plant tissue culture, our study delves into the comparative effectiveness of the four models used in two distinct culture systems, namely the TIS and semisolid medium.…”
Section: Machine Learning Analysissupporting
confidence: 92%
“…Our research underscores the superior predictive performance of RF in the TIS culture, particularly in forecasting the number of microcorms, shoots, and roots. This finding is consistent with the literature, such as Şimşek [35], which highlighted the robustness of RF in detecting water stress effects in strawberries, and Aasim et al [37], which identified the efficacy of RF in predicting germination and morphological traits in hemp seedlings. The ability of RF to…”
Section: Machine Learning Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…The application of machine learning (ML) is prevalent in solving complex problems across diverse scientific disciplines [25]. Despite its widespread use in various fields, the adoption of ML methodologies in plant and agricultural science is comparatively limited [26].…”
Section: Introductionmentioning
confidence: 99%